The use and function of scripture in 1 Maccabees - Choi, Dongbin (The Library of Second Temple Studies, 2020)
Cover -- Title -- Copyright -- Contents -- Acknowledgements -- Abbreviations -- Chapter 1 Introduction -- 1.1. General introduction -- 1.2. Literature review -- 1.2.1. Functionality of Scripture in 1 Maccabees -- 1.2.2. Scripture, fulfilment of Israel's hope, and the role of the Hasmoneans -- 1.2.3. Jewish perception of the past -- 1.2.4. Summary -- 1.3. Aims and outline of the present study -- 1.4. Methodology -- Chapter 2 The Contribution of the Literary, Social and Cultural Milieus on the Appropriation of Scripture in 1 Maccabees -- 2.1. Textual issues -- 2.1.1. Textual variance -- 2.1.2. The lost Hebrew original text -- 2.1.3. On Greek Scripture -- 2.1.4. The Translator's vocabulary -- 2.1.5. Summary -- 2.2. Authorship and dating of 1 Maccabees -- 2.2.1. Authorship -- 2.2.2. Dating of 1 Maccabees -- 2.3. Availability of Scripture at the time of 1 Maccabees -- 2.3.1. 'The Law and the Prophets (and other writings)' -- 2.3.2. Conclusion -- 2.4. Hellenization and the influence of Scripture in 1 Maccabees -- 2.4.1. A conceptual issue -- 2.4.2. Internal features relating to Hellenism -- 2.4.3. External features relating to Hellenism -- 2.4.4. Summary -- 2.5. Jewish perception of the past -- 2.5.1. Biblical and early Jewish literature -- 2.5.2. 1 Maccabees -- 2.5.3. Conclusion -- Chapter 3 The Use of Scripture in 1 Maccabees: Philological Parallels -- 3.1. Introduction -- 3.2. Analysis of Lange and Weigold's biblical references in 1 Maccabees -- 3.3. Results -- 3.3.1. Features of philological parallels -- 3.3.2. Classification of the parallels -- 3.3.3. Result: a revised list of philological parallels -- Chapter 4 The Use of Scripture in 1 Maccabees: Conceptual Parallels -- 4.1. The Deuteronomic covenantal framework -- 4.1.1. Deuteronomy -- 4.1.2. 1 Maccabees -- 4.1.3. Summary -- 4.2. Biblical judges -- 4.2.1. Morphological association.